PENGARUH CR, DER DAN TATO TERHADAP PBV DENGAN ROA SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR PADA BEI TAHUN 2010-2014) - Wahyu Adi Sutrisno; Yulianeu Yulianeu; Patricia Diana Paramitha (Universitas Pandanaran, 2016)
The purpose of this research is to find out the factors of independent variables to dependen variable inproperty real estate company in 2010-2014. Price to book value (PBV) is the dependent variable in thisresearch. There are three independent variables used to support this research, namely current ratio (CR), debtto equity ratio (DER), total asset turnover (TATO), and return on asset (ROA) as intervening variable. The firstanalysis is to find out factors variable CR, DER and TATOeffect on ROA. Second is to find out factors variableCR, DER, TATO and ROA effect on PBV and the last is to find out factors variables CR, DER, TATO effect onPBV with ROA as intervening variable.The population used in this research consists of all companies engaged in property real estate period2010-2014. The total population are 43 companies. Sampling method in this research use purposive samplingwhich resulted sample into 25 company of property sector real estate. Data analysis method used wasdescriptive analysis, classical assumption test, multiple linear regression, goodness of fit test, and using pathanalysis technique in SPSS 17 program.The result of ROA as dependent variable shows that CR and DER variable have no effect on ROA, WhileTATO has a positive and significant effect on ROA. Then for the PBV variable as the dependent variable, it wasfound that CR had negative and significant effect on PBV. DER and TATO have no effect on PBV. While ROAaffects PBV. While the results of research on the influence of mediation ROA showed that ROA does not mediatethe influence between CR, DER and TATO against PBV.Key word: Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Asset(ROA) and Price to Book Value (PBV)